Decoding exchange rate in emerging economy: Financial and energy dynamics - Saif Ullah; Haitham Nobanee (Heliyon)
This research paper examines the financial and energy-related factors influencing the exchange rate in Pakistan, focusing on currency depreciation or appreciation between July 2006 and June 2021. The Autoregressive Distributed Lag (ARDL) Bounds Test is employed to analyze both short- and long-run dynamics. The findings reveal that foreign direct investment (FDI) supports strengthening the exchange rate, addressing concerns about short- and long-term profitability. Energy factors, such as fuel prices, positively impact the exchange rate in both the short and long term. Conversely, stock market declines and rising inflation are associated with significant changes in the exchange rate, including currency depreciation. Interestingly, remittances exhibit a complex relationship with the exchange rate, potentially resulting in adverse effects if not managed effectively. The study provides balanced policy implications for sustainable financial and energy development in emerging economies.